The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1074/jbc.m115.711242
|View full text |Cite
|
Sign up to set email alerts
|

The Stability and Expression Level of Bok Are Governed by Binding to Inositol 1,4,5-Trisphosphate Receptors

Abstract: Bok is a member of the Bcl-2 protein family that governs the intrinsic apoptosis pathway, although the role that Bok plays in this pathway is unclear. We have shown previously in cultured cell lines that Bok interacts strongly with inositol 1,4,5-trisphosphate receptors (IP 3 Rs), suggesting that it may contribute to the structural integrity or stability of IP 3 R tetramers. Here we report that Bok is similarly IP 3 R-assocated in mouse tissues, that essentially all cellular Bok is IP 3 R bound, that it is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 55 publications
3
104
0
Order By: Relevance
“…BOK has been shown to interact with IP3 receptors, protecting IP3Rs from caspase‐mediated degradation and BOK from proteasomal degradation . Degradation of BOK via the ubiquitin/proteasome was also shown by Llambi et al .…”
Section: Introductionmentioning
confidence: 76%
“…BOK has been shown to interact with IP3 receptors, protecting IP3Rs from caspase‐mediated degradation and BOK from proteasomal degradation . Degradation of BOK via the ubiquitin/proteasome was also shown by Llambi et al .…”
Section: Introductionmentioning
confidence: 76%
“…Consistent with this interpretation, BOK inhibited TGF-β2-induced cell migration, as assessed by Boyden chamber migration assay (Figure 5c). Furthermore, we detected TGFβ2-induced increase of ATF4 as well as a shorter form of BOK that lacks the N-terminus due to alternative translation initiation at Met 15 (13); ATF4, being required for cell invasion (24), was slightly diminished in TGFβ2-treated cell upon additional BOK overexpression and was accompanied by reduction of the shorter form of BOK (Figure 5e). …”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we found that BOK levels were significantly decreased in tumors of lymph node positive patients and in less differentiated tumors compared to adjacent lung parenchyma (Figure 1b). This phenotype might be favoured by epigenetic mechanisms during tumor progression (Figure 3, 33) and/or by proteasome-dependent regulation of BOK levels (1, 13). Importantly, we found a poor correlation between BOK mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has indicated that Bok interacts strongly with IP3Rs and may contribute to the structural integrity or stability of IP3R tetramers (Schulman et al 2013). In return, Bok is dramatically stabilized by binding to IP3Rs and the proapoptotic effects of overexpressed Bok could be limited (Schulman et al 2016). PKB/Akt, which is a well-known prosurvival factor, exerts critical neuroprotective effects by phosphorylating downstream targets after TBI.…”
Section: Ip3rsmentioning
confidence: 97%